2021
DOI: 10.1039/d1ta05648d
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt phosphide supported by two-dimensional molybdenum carbide (MXene) for the hydrogen evolution reaction, oxygen evolution reaction, and overall water splitting

Abstract: CoP/Mo2CTx is prepared as efficient catalyst for HER, OER, and water splitting. DFT calculations revealed that it has optimal H* adsorption free energy and MXene plays a critical role to boost HER, while CoP is transformed into Co–OOH in OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…In contrast, the post-OER sample still showed three peaks but with significantly reduced intensity (Figure 7E), confirming that CoP was converted into CoOOH, accordance with previous studies [56,60]. Figure 7F shows the high-resolution O 1s spectrum, and the peaks at 529.53, 531.1, and 533 eV correspond to the Co O bond, hydroxides, and adsorbed oxygen, respectively [57].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, the post-OER sample still showed three peaks but with significantly reduced intensity (Figure 7E), confirming that CoP was converted into CoOOH, accordance with previous studies [56,60]. Figure 7F shows the high-resolution O 1s spectrum, and the peaks at 529.53, 531.1, and 533 eV correspond to the Co O bond, hydroxides, and adsorbed oxygen, respectively [57].…”
Section: Resultssupporting
confidence: 88%
“…30‐0443). These results demonstrate that CoP is converted to (oxy)hydroxide, which is the real active species of OER [56‐58]. Raman spectra is also employed to investigate the changes of crystal structure and crystallinity for the CoP NWs/CoP NPs@NC/CC sample before and after OER.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this strategy, organic solvents (i.e., octadecene and oleylamine) are adopted to promote the adsorption, nucleation and growth of nickel phosphide toward numerous defects on the surfaces of nano Ti 3 C 2 T x MXene, which is different from the conventional synthesis of metal phosphide on MXene from a facile precipitation reaction and phosphorization process. [30][31][32] It was found that the significant tensile strain of the Ni 2 P lattice exists at the interface between Ni 2 P NSs and Ti 3 C 2 T x MXene. Our density functional theory (DFT) calculations show that the presence of interfacial strain between Ni 2 P and Ti 3 C 2 T x MXene shifts the hydrogen adsorption energy close to the optimal value (0.00 eV), which leads to the high HER activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TMCs and TMNs present promising catalytic functions in tuning the kinetic features of the Li–S system. Furthermore, these compounds are considered proper adsorbents through forming metal–sulfide bonds with moderate adsorptive energy, in case where excessive immobilization of the intermediate will impair the continuous electrochemical reaction due to the sluggish redox kinetics. A heterojunction, in combination of two materials with separate electronic structures, has been widely used in regulation of electrical properties of semiconductors. The design concept of a heterostructure can also be utilized in electrochemical devices and has attracted much attention. Due to modulation of two different materials at the molecular level, the heterostructure combines the merits of the two and further activates new features at the reactive heterointerface.…”
Section: Introductionmentioning
confidence: 99%